Rural Tourism Product Planning "Nepal Van Java", Dusun Butuh, Magelang Regency - Mega Mega Aldora; Endah Trihayuningtyas; Ikhsan Ardiansyah; Nisa Aulia Nur Setiawan; Agrestasha Nursavira Lim; Rifa Agustina Salsabila; Muhammad Richard Oktaviano (Journal of Tourism Sustainability, 2021)
Nepal Van Java is a tourism attraction that offers the beauty of local residences in Mount Sumbing slope located in Dusun Butuh, Magelang. According to a simple calculation of average visits up to a thousand visitors in one day, Nepal Van Java has a high visitors number according to a simple estimate of average visits. However, at this time, there are not many rural tourism products offered by Nepal Van Java because this destination is still in the planning stage where there is no planning for rustic tourism products. The purpose of this paper is to describe the planning process related to the village tourism product. Qualitative research methods have applied to this research, resulting in an understanding of the actual condition of village tourism products. Detailed planning related to Nepal Van Java tourism products includes planning on facilities, transportation systems, and introduction of visitors, with the idea of focusing on optimizing agricultural resources as agrotourism, potential aids for farm stays, and culture.